The Plasmodium vivax rhoptry neck protein 5 is expressed in the apical pole of Plasmodium vivax VCG-1 strain schizonts and binds to human reticulocytes (2015)
Background: Different proteins derived from the membrane or the apical organelles become involved in malarial parasite invasion of host cells. Among these, the rhoptry neck proteins (RONs) interact with a protein component of the micronemes to enable the formation of a strong bond which is crucial for the parasite's successful invasion. The present study was aimed at identifying and characterizing the RON5 protein in Plasmodium vivax and evaluating its ability to bind to reticulocytes. Methods: Taking the Plasmodium falciparum and Plasmodium knowlesi RON5 amino acid sequences as template, an in-silico search was made in the P. vivax genome for identifying the orthologous gene. Different molecular tools were used for experimentally ascertaining pvron5 gene presence and transcription in P. vivax VCG-1 strain schizonts. Polyclonal antibodies against PvRON5 peptides were used for evaluating protein expression (by Western blot) and sub-cellular localization (by immunofluorescence). A 33 kDa PvRON5 fragment was expressed in Escherichia coli and used for evaluating the reactivity of sera from patients infected by P. vivax. Two assays were made for determining the RON5 recombinant fragment's ability to bind to reticulocyte-enriched human umbilical cord samples. Results: The pvron5 gene (3,477 bp) was transcribed in VCG-1 strain schizonts and encoded a ~133 kDa protein which was expressed in the rhoptry neck of VCG-1 strain late schizonts, together with PvRON2 and PvRON4. Polyclonal sera against PvRON5 peptides specifically detected ~85 and ~30 kDa fragments in parasite lysate, thereby suggesting proteolytic processing in this protein. Comparative analysis of VCG-1 strain PvRON5 with other P. vivax strains having different geographic localizations suggested its low polymorphism regarding other malarial antigens. A recombinant fragment of the PvRON5 protein (rPvRON5) was recognized by sera from P. vivax-infected patients and bound to red blood cells, having a marked preference for human reticulocytes. Conclusions: The pvron5 gene is transcribed in the VCG-1 strain, the encoded protein is expressed at the parasite's apical pole and might be participating in merozoite invasion of host cells, taking into account its marked binding preference for human reticulocytes. © 2015 Arévalo-Pinzón et al.; licensee BioMed Central.